Sports financing by local government units in Poland – case study - Kowalczyk, Kacper (Journal of Finance and Financial Law, 2019)
The article contains information on the concept of sport and physical culture and their financing by local government units. Nowadays sport is ubiquitous. For some people it is a way to spend free time, relax, take care of health, while for others it is a source of earnings. Providing the right conditions for its cultivation is an important aspect of the activities of central and local authorities. Providing adequate sports infrastructure is key to ensure its development and ensure appropriate legal and financial conditions at the lowest levels of the structure of public authorities. Local government units face the problem of obtaining funds to finance sport and their appropriate distribution. The purpose of the article is to present the budget expenditure of the Skierniewice Commune for sport and physical culture, as well as the evaluation of the method of distribution of funds by local government units.